Yoga or Mindfulness on Diabetes: Scoping Review for Theoretical Experimental Framework - Cangelosi, Giovanni; Acito, Mattia; Grappasonni, Iolanda; Nguyen, Cuc Thi Thu; Tesauro, Marina; Pantanetti, Paola; Morichetti, Luciana; Ceroni, Enrico; Benni, Andrea; Peterelli, Fabio (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. About one in 11 adults worldwide suffers from diabetic disease with constantly increasing prevalence; from the 529 million patients registered in 2021, the number of people with diabetes was predicted to rise to approximately 1.31 billion in 2050. In Italy, 5.9% of the population is diabetic, with a higher prevalence with increasing age and in the South of the country. Yoga and Mindfulness could represent a valid support for the care of diabetic subjects especially in a stressful caring context such as the Covid-19 pandemic.Study Design. A scoping review was conducted to achieve the goals of the study. Yoga or Mindfulness interventions on diabetic subjects were specifically analyzed and qualitative-quantitative data collected in the selected randomized controlled trials were extensive for possible meta-analysis.Methods. The review was conducted by two independent practitioners and a third one was consulted in case of conflict. The PRISMA method was used for both the selection and reporting of the studies to be included. Specific PICOS and search strategies have been developed on PubMed, Embase and PsycINFO databases. Included in the review were: randomised controlled trials, full dissertation articles and papers in English with a time limit on May 31, 2022.Results. The Review included 22 studies; 12 on Mindfulness, 9 on Yoga and one about both disciplines; among these, one studied patients with Type 1 Diabetes, 14 with Type 2 Diabetes, 6 with both and one with Gestational Diabetes. Only one paper studied adolescent subjects while the other 21 focused on a range of adult subjects. The studies showed that Yoga and Mindfulness have strong potential not only on stress management, but also on clinical-metabolic parameters.Conclusions. The recent Covid-19 pandemic has certainly redesigned a new way of treating and managing chronic diseases, such as diabetes. An increasingly fragile population, and with the growing need to reduce overall stress levels, could find alternative practices in Yoga and Mindfulness to support conventional therapies.